Challenges in comparing the acute cognitive outcomes of high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) vs. electroconvulsive therapy (ECT) in major depression: A systematic review. (August 2017) - Kedzior, Karina Karolina; Schuchinsky, Maria; Gerkensmeier, Imke; Loo, Colleen
Abstract: The present study aimed to systematically compare the cognitive outcomes of high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) and electroconvulsive therapy (ECT) in head-to-head studies with major depression (MDD) patients. A systematic literature search identified six studies with 219 MDD patients that were too heterogeneous to reliably detect meaningful differences in acute cognitive outcomes after ECT vs. HF-rTMS. Cognitive effects of brain stimulation vary depending on the timeframe and methods of assessment, stimulation parameters, and maintenance treatment. Thus, acute and longer-term differences in cognitive outcomes both need to be investigated at precisely defined timeframes and with similar instruments assessing comparable functions. Highlights: ECT and HF-rTMS have similar cognitive outcomes in six head-to-head studies. These results might be due to heterogeneous timing and assessment methods. Cognitive effects need to be assessed in longer-term after brain stimulation.